2010
DOI: 10.1016/j.gene.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pluripotency-associated genes in the surviving fraction of cultured human embryonic stem cells is not significantly affected by ionizing radiation

Abstract: Human embryonic stem cells (hESC) are capable of give rise to all cell types in the human body during the normal course of development. Therefore, these cells hold a great promise in regenerative cell replacement based therapeutical approaches. However, some controversy exists in literature concerning the ultimate fate of hESC after exposure to genotoxic agents, in particular, regarding the effect of DNA damaging insults on pluripotency of hESC. To comprehensively address this issue, we performed an analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
7
28
1
Order By: Relevance
“…It was documented that IR exposure results in fast apoptosis of hESC671112. To confirm these observations in our cell culture conditions we used a fluorescent peptide-based assay to detect activated Caspase 3/7.…”
Section: Resultssupporting
confidence: 67%
“…It was documented that IR exposure results in fast apoptosis of hESC671112. To confirm these observations in our cell culture conditions we used a fluorescent peptide-based assay to detect activated Caspase 3/7.…”
Section: Resultssupporting
confidence: 67%
“…33 hESC after irradiation in doses known to induce apoptosis of these cells are able to generate teratomas and express pluripotent genes. 34,35 In our experiments hESC exposed to sublethal heat shock easily underwent apoptosis, but survived cells rapidly restore their initial properties: morphology, high proliferation activity, pluripotent properties (expression of pluripotent markers, generation of embryoid bodies and differentiation into three germ layers). Differentiated fibroblast-like cells that survived heat shock also resumed proliferation and underwent RS simultaneously with their parental cells, i.e., restore initial cell properties.…”
Section: Methodsmentioning
confidence: 69%
“…Cell were incubated for 30 min at 37 °C in the dark. Stained cells were observed with the Zeiss Axiovert 200 fluorescence microscope 6 .…”
Section: Methodsmentioning
confidence: 99%
“…During the past decade considerable knowledge was gained regarding the effects of IR on hESC 5 . It was shown that hESC are very sensitive to IR; the exposure to a relatively low dose of 1 Gy results in death of almost 30% of the cells 6 . The immediate effect of IR exposure of these cells is apoptosis; however, the surviving cells retain their pluripotency markers and ability to form all three embryonic germ layers as was evidenced by teratoma formation assay [6][7][8] .…”
mentioning
confidence: 99%